Development of High-Performance Ethanol Gas Sensors Based on La2O3 Nanoparticles-Embedded Porous SnO2 Nanofibers - Gen Li; Jian Hou; Muhammad Hilal; Hyojung Kim; Zhiyong Chen; Yunhao Cui; Jun-Hyun Kim; Zhicheng Cai (Sensors)
Porous pure SnO2 nanofibers (NFs) and La2O3 nanoparticles (NPs)-embedded porous SnO2 NFs were successfully synthesized via electrospinning followed by calcination. These materials were systematically evaluated as gas-sensing elements in metal-oxide-semiconductor (MOS) sensors. The La2O3 NPs embedded in porous SnO2 NFs demonstrated superior gas-sensing performance compared to pure SnO2 NFs. Specifically, the incorporation of La2O3 resulted in a 12-fold enhancement in gas-sensing response towards ethanol, significantly improving both sensitivity and selectivity by tuning the carrier concentration and modifying oxygen deficiencies and chemisorbed oxygen levels. Thus, La2O3 NPs embedded in SnO2 NFs present a promising strategy for the development of high-performance ethanol gas sensors.